Phenotypic variability of fruits of Caryocar brasiliense Cambess in three different physiognomies of the Cerrado, in the sate of Tocantins, Brazil. - Ramos, Bárbara Helena (2015)
The objective of this study was to assess the phenotypic diversity of Caryocar brasiliense Cambess through morphological analysis of the fruit in three different Cerrado physiognomies: dense, typical and thin. In each vegetation type 20 genotypes were randomly sampled in order to collected 20 fruits per genotype. The vegetation types that have greater variability were the dense and the thin Cerrado, featuring four subgroups of phenotypic similarity accordingly to the clustering method (UPGMA), drawn from the matrix of Euclidean distances between standardizedmean. Greater similarities were clearly observed between the fruits collected in the dense and in the typical cerrado physiognomies in comparison with the thin Cerrado fruits. The intrapopulational variability was higher than those observed between the vegetation types,which may be the result of the environmental variation.